Agenesis of the Right Hepatic Lobe - Lucas Souto Nacif; Yuri dos Santos Buscariolli; Luiz Augusto Carneiro D'Albuquerque; Wellington Andraus (Case Reports in Medicine)
Introduction. Agenesis of the right lobe of the liver is a rare finding and was defined as the absence of liver tissue on the right side, with preservation of the middle hepatic vein, without previous disease or surgery. It is usually an incident finding reveled by imaging exams or during abdominal surgery. Case Report. A 32-year-old male patient was admitted to the hospital for abdominal discomfort and loss of appetite. Imaging studies revealed the absence of the right hepatic lobe and hypertrophied left hepatic segments. Discussion. Anomalies of hepatic morphology are rare and correspond to developmental defects during embryogenesis, are a rare diagnosis, and are generally diagnosed incidentally based on imaging. Agenesis or hypoplasia of the right lobe may predispose the patient to the development of portal hypertension and esophageal varices. Surgical knowledge of such anatomical agenesis is necessary for surgical planning, for the appropriate identification of intraoperative surgical findings, and for the design of the postoperative approach to therapy. Conclusion. Agenesis of the right hepatic lobe is a rare condition. We want to highlight the importance of understanding the condition. Surgeons must recognize the entity in order to deal appropriately with the findings.